(untitled) (Philadelphia, 2001)
Harvard Medical School, Boston, MA. Revised reprint of Allergic Diseases of the Eye, c2000, a Brandon/Hill Medical List selection (#379). Addresses relevant new developments in the field of ocular allergy. Discusses clinical manifestations and treatments available now and in the near future. First edition listed week 2000-23. DNLM: Eye Diseases--Immunology.
Keywords: Eye,Eye diseases,Allergy,Mắt,Mắt bệnh,Dị ứng; Diseases,Immunological aspects,Immunology,Bệnh,Khía cạnh miễn dịch học,Sự làm miễn dịch